The unity of pathological existential feelings and the emergence of doubt - Lopes, Marcelo Vieira (Voluntas: Revista Internacional de Filosofia, 2025)
In this work, I discuss the concept of existential feelings recently developed by Matthew Ratcliffe in three steps. First, I examine the concept, taking into account its initial formulation and internal aspects. After presenting how this affective dimension resists the traditional body/cognition dichotomy in classical philosophy of emotion, I draw attention to the inconspicuous nature of these feelings and its structuring role in our intentional life. While it includes bodily elements that can be identified and described, its significance becomes most apparent when its proper functioning is disrupted. The unfolding of an ordinary experience, its “normality”, thus depends on a level of habituality and normalcy in which these feelings are not manifest. Second, I analyze the assumption that cases of illness provide us with a lens through which to access this tacit dimension. In line with Ratcliffe, I argue that psychiatric disorders offer a privileged standpoint for grasping this affective-structural dimension of our intentional life. However, despite their apparent diversity, I argue that pathological existential feelings must share something if they are to be clinically relevant. So, third and finally, I argue for a kind of unity underlying pathological existential feelings in psychiatric disorders. I propose that a distinctive sense of doubt can be meaningfully attributed to the lived experience of these conditions. The implications of this notion for a phenomenologically informed psychiatry are also explored.